Programa gráfico livre para a análise de lajes de edificações de concreto armado usando o modelo de grelha equivalente - Cass, Andrew John Richter (2015)
It’s presented in this work a graphic program that allows the analysis (calculation of forces and displacements) of concrete slabs by the equivalent grid model. The surface is considered as monolithic without the traditional discretization of the structure, i.e., the separation of the various structural members (beams, columns and slabs). Only the pillars are considered as unmovable in the direction of its principal axis. The graphical environment designed for this is pioneering, developed by objectoriented programming and will be distributed freely and with listings available. The system allows the designing of the structure as a model, allowing an easier perception of its different structural components and the definition of the different stresses on it. The program establishes an interface adapted to the calculation module, that initially was developed by Igor Stayanov Cotta in 2006,.and thus allows the graphic view of the efforts, displacements and stresses acting over the model.